Worklife Balance and Burnout Impact on PT. PERTAMINA (Persero) RU VI Balongan Employee Performance - Aisyah, Nur; Langen Pujiwati, Ratu Sekar; Maulana, Syaikh; Prasetya, Budi Agung (PT. Riset Press International, 2024)
This research aims to examine the influence of work-life balance and burnout on employee performance. This research is quantitative. The sample in this study was several office employees at PT. Pertamina RU VI Balongan. The sampling technique used was the Slovin technique by taking 0.01 from the existing population. Data collection was obtained by distributing questionnaires and direct observation. The analysis technique used is multiple linear regression analysis. Based on the research results, it shows that simultaneously work-life balance (X1) has a significant effect on employee performance (Y), and burnout (X2) has a negative and significant effect on employee performance (Y) for employees PT. Pertamina RU VI Balongan.